TWINNING IN CAMELS - Tinson, A. H.; Kuhad, K. S.; Singh, K.; Sambyal, R.; Mugheiry, A.; Rahman, A.; Masri, J. Al (Emirates Journal of Food and Agriculture, 2017)
Please see the scanned pdf version in full text